UPAYA GURU DALAM MENINGKATKAN PEMAHAMAN SERTA KEMAMPUAN BERFIKIR KRITIS SISWA PADA MATA PELAJARAN FIQIH KELAS 8 DI MTS ST GUGUAK RANDAH - Al Hilal Isra; M. Isnando Tamrin; Mira Husni (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2024)
A teacher is someone who contributes to education. Without the services of a teacher, students will not be able to know knowledge. In living life, a Muslim must have knowledge related to his daily life. With this knowledge, someone will be able to know about the laws or rules taught by Islam. The knowledge of these laws is summarized in a discussion called fiqh. At MTs ST Guguak Randah, learning activities in fiqh subjects in class 8 tend to be active and students can understand the learning more quickly, as well as increasing students' critical thinking skills regarding the fiqh material being studied. Due to the efforts made by the teacher during the learning process.